2021
DOI: 10.5171/2021.110411
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions towards Cryptocurrency Adoption: A case of Saudi Arabian Citizens

Abstract: The global financial market is influenced by relatively new technologies such as cryptocurrencies; namely Bitcoin, Ethereum, Litecoin, and others. Cryptocurrencies are a challenging area in finance that requires additional attention from the academic community as they can have a potentially large impact on society and the economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In the studies conducted in the literature, there are results that the perceived usefulness level positively affects the customers' intention to use (Luarn & Lin, 2005;Ramayah & Ignatius, 2005;Paçan Özcan et al, 2019;Lee, 2009;Çetinsöz, 2015). The effect of perceived usefulness on the intention to use the cryptocurrency (Nadeem et al, 2021) and acceptance (Alaklabı & Kang, 2021) is significant. Retailers' net transactional benefits, as well as consumer demand in e-commerce, have a significant effect on both the intention to accept crypto payments and the actual adoption of crypto payments (Jonker, 2019).…”
Section: Perceived Usefulnessmentioning
confidence: 98%
“…In the studies conducted in the literature, there are results that the perceived usefulness level positively affects the customers' intention to use (Luarn & Lin, 2005;Ramayah & Ignatius, 2005;Paçan Özcan et al, 2019;Lee, 2009;Çetinsöz, 2015). The effect of perceived usefulness on the intention to use the cryptocurrency (Nadeem et al, 2021) and acceptance (Alaklabı & Kang, 2021) is significant. Retailers' net transactional benefits, as well as consumer demand in e-commerce, have a significant effect on both the intention to accept crypto payments and the actual adoption of crypto payments (Jonker, 2019).…”
Section: Perceived Usefulnessmentioning
confidence: 98%
“…Cryptocurrencies are to eliminate paper currency from the marketplace and to create an arrangement that frees from the state government's supervision and control (Alaklabi and Kang, 2021). Cryptocurrency depends on blockchain technology, which can address the difficulty of achieving end-to-end transparency.…”
Section: Cryptocurrencymentioning
confidence: 99%
“…Additionally, when it comes to bitcoin acceptance in Saudi Arabian, it was shown that subject norms, security risk, perception of utility, and enjoyment do influence the acceptance and utilization of bitcoin among Saudi Arabian citizens [47]. Another study demonstrated that intrinsic motivation in terms of hedonic motivation is important in the adoption of blockchain technology (bitcoin), while extrinsic motivations such as performance expectancy are a significant predictor of bitcoin use [48].…”
Section: Empirical Studies On Bitcoinmentioning
confidence: 99%